Sufistic Education Based on Karamah of Syaikhana Muhammad Kholil Bangkalan - Ulum, Khoirul; Sodiq, Akhmad; Dimyati, Dimyati (Maharot : Journal of Islamic Education, 2025)
This article explores the model of Sufi-based education practiced by Syaikhana Muhammad Kholil of Bangkalan, a charismatic Islamic scholar renowned for his sainthood (maq?m al-wil?yah) and spiritual charisma (kar?mah). The study focuses on his approach to spiritual formation, which goes beyond formal-institutional structures and emphasizes the inner relationship between murshid (spiritual guide) and mur?d (disciple). Using a qualitative descriptive method and literature review, this article reveals that Syaikhana Kholil’s educational model was rooted in exemplary conduct, prayer, spiritual discipline, and deep mystical experiences. His karamah is seen not merely as supernatural phenomena, but as an educational tool for shaping the spiritual character of his students. This model reflects a form of esoteric and transcendental knowledge transmission, based on inner unveiling (muk?shafah). The study concludes that Syaikhana Kholil’s karamah-based Sufi education represents a unique form of tarbiyah in the pesantren tradition, capable of producing intellectually and spiritually mature scholars and da'wah figures.